Peran Pustakawan dalam Program Transformasi Perpustakaan Berbasis Inklusi Sosial di Provinsi Sulawesi Selatan - Ridwan, Irma Ningsih; Mathar, M. Quraisy; Iskandar, Iskandar (Prodi Perpustakaan dan Sains Informasi, 2025)
This study aims to determine the role of librarians in the Social Inclusion-Based Library Transformation Program (TPBIS) in South Sulawesi. This study is descriptive with a qualitative approach. The subjects of this study were 10 librarians who were regional facilitators in South Sulawesi. The results of the study indicate that the role of librarians as regional facilitators The role of librarians as regional facilitators in South Sulawesi is to implement program strategies in district/city public libraries and also to provide assistance and mentoring to village/sub-district libraries in ensuring the implementation of the TPBIS program. Internal challenges faced by librarians are human resources, budget, facilities and infrastructure, leadership support and the impact of TPBIS activities. Meanwhile, the challenges for librarians in mentoring village/sub-district libraries are communication factors, commitment and motivation of library managers, and support from village/sub-district heads. The librarian's strategies in overcoming these challenges are to conduct advocacy, promotion, meetings, and demonstrate the impact of the program. The impact of the role of librarians as regional facilitators is the development of librarians' self-capacity, a positive image of the librarian profession, a paradigm change towards libraries, and increased public literacy.